From interfaith harmony to religious moderation education: A conceptual model from the Jetayu area, Pekalongan, Indonesia - Lidya Arafah; Dini Valencia Kholifatun Khasanah; Navilatul Maimunah; Abidatul Dhulkamala; Mutiara Aqila; Zalfa Zahirotul Jannah; Elok Nailuna; Farah Amelia Efendi; Ika Ismatul Hawa; Arditya Prayogi (Eduvista: Journal of Education and Innovation, 2026)
Interfaith harmony has been widely examined as a form of social cohesion; however, its role as a foundation for religious moderation education within multicultural public spaces remains underexplored. This study aims to analyze interfaith harmony practices in the Jetayu Area, Pekalongan City, as a basis for religious moderation education through the perspective of the four pillars of religious moderation. A qualitative case study approach was employed using observation, in-depth interviews with seven informants, document analysis, and the interactive analysis model of Miles, Huberman, and Saldaña. The findings reveal that interfaith communication, shared public space management, community participation, and local cultural values foster interfaith harmony that internalizes national commitment, tolerance, anti-violence, and accommodation toward local culture. This study contributes by proposing the conceptual model Religious Moderation Education through Interfaith Harmony in Public Multicultural Space as a new perspective for developing community-based religious moderation education. Abstrak Harmoni lintas iman telah banyak dikaji sebagai bentuk kerukunan sosial, namun perannya sebagai basis pendidikan moderasi beragama di ruang publik multikultural masih belum banyak dijelaskan. Penelitian ini bertujuan menganalisis praktik harmoni lintas iman di Kawasan Jetayu, Kota Pekalongan, sebagai basis pendidikan moderasi beragama melalui perspektif empat pilar moderasi beragama. Penelitian ini menggunakan pendekatan kualitatif dengan desain studi kasus melalui observasi, wawancara mendalam terhadap tujuh informan, studi dokumentasi, serta dianalisis menggunakan model analisis interaktif Miles, Huberman, dan Saldaña. Hasil penelitian menunjukkan bahwa komunikasi lintas iman, pengelolaan ruang publik bersama, partisipasi masyarakat, dan nilai budaya lokal membentuk harmoni lintas iman yang menginternalisasi komitmen kebangsaan, toleransi, anti-kekerasan, serta sikap akomodatif terhadap budaya lokal. Penelitian ini berkontribusi dengan menawarkan model konseptual Religious Moderation Education through Interfaith Harmony in Public Multicultural Space sebagai perspektif baru dalam pengembangan pendidikan moderasi beragama berbasis masyarakat.